Cecília Meireles e o existencialismo Feminino - Lima, Denise Gomes (2014)
The objective of this research is to reflect on the female in existentialism poems by Cecilia Meireles cecilianos analysis of poetic texts that seeks to understand some fundamental aspects of the manifestation of existentialism in Ceciliana work. To achieve this goal, we propose the following questions: a refined and uneasy feeling about the other leads to life and poetry of Cecilia Meireles to the philosophical aspect of existentialism; awareness of finitude and human frailty, treated with extreme sensitivity implies the female character of his poetry , the lyrical poet-subjective engagement with the things you see, oblivious to time, sometimes the space, demonstrating their passive character before the events, however, the act of thinking about them makes this passivity is also a activity. From these reflections, the poet develops his inquiries about his being and his place as a woman. Based research in relation to the concept of existentialism, the thought of Soren Kierkeggard and Jean Paul Sartre, about the concept of feminine, use texts Ana Cristina Cesar, Jacicarla Souza Da Silva, Fernanda Queiroz Ribeiro de Oliveira, Norma Telles and Guacira Lopes Louro. Among the search results, we emphasize that the different faces of the female existentialism found in the poems of Cecilia Meireles allow us to observe the peculiarities not only gender, but also their own way of understanding literary creation as the result of a new possibility of contact and ( re) familiarize yourself